Penggunaan Analytical Hierarchy Process (AHP) pada Penentuan Prioritas Supplier Food Chemical di PT. Garuda Hidrotive Internasional - Hadiwijaya, Nehemia; Sundari, Jenie (Elinvo (Electronics, Informatics, and Vocational Education), 2020)
Abstract-Supplier selection is one of the important things in purchasing activities for companies. Supplier selection is a multi-criteria problem which includes quantitative and qualitative factors. One method that can be used for supplier selection is the AHP (Analytical Hierarchy Process) method. The problems that will be discussed in this study are: (1) how is the order of priority criteria and sub-criteria in the selection of suppliers at PT Garuda Hidrotive International? (2) which supplier / supplier should PT Garuda Hidrotive International choose based on the AHP method? The sampling technique uses judgment sampling because the AHP method requires dependence on a group of experts according to the types of specialists involved in decision making. Based on the results of the analysis, the advice that can be given is, if the company will develop a partnership with suppliers, the company is preferred to choose supplier X as a supplier food chemical for the company because supplier X is the best supplier that has the highest overall value. With this partnership, the supply chain performance between suppliers and companies will be better and can facilitate the overall production activities.